2018
DOI: 10.1002/ceat.201700676
|View full text |Cite
|
Sign up to set email alerts
|

Antisolvent Crystallization of Polymorphs of L‐Histidine

Abstract: Antisolvent crystallization is the most common method to study solvent effects on polymorphic crystallization. L‐Histidine (L‐his) served as a model substance. Acetonitrile, acetone, and methanol were selected as antisolvents, with water as solvent. The formation of L‐his polymorphs in antisolvent crystallization as a function of supersaturation, antisolvent volume fraction, and temperature was studied. The solubility of polymorph A of L‐his decreased with increasing volume fraction of antisolvent and increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 25 publications
(29 reference statements)
3
14
0
Order By: Relevance
“…The obtained photomicrographs of the prepared crystals of forms A and B indicated that the crystals of form A exhibited rod‐like shapes consistent with those reported in previous works , , . The shape of crystals of form B appeared plate‐like like those reported in former works , , .…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…The obtained photomicrographs of the prepared crystals of forms A and B indicated that the crystals of form A exhibited rod‐like shapes consistent with those reported in previous works , , . The shape of crystals of form B appeared plate‐like like those reported in former works , , .…”
Section: Resultssupporting
confidence: 88%
“…Pure crystals of form A of L ‐his were produced from aqueous solution crystallization by cooling operation at 25 °C as described in previous works , , , . A saturated aqueous solution of L ‐his at 45 °C was prepared at 50 °C and then the solution was cooled rapidly to 10 °C.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations